An exploration of the determinants of bribery in Benin’s transborder trade - Bensassi, Sami; Jarreau, Joachim; Mitaritonna, Cristina (International Food Policy Research Institute, 2016)
Few studies give a systematic account of the bribes paid by smugglers to different groups of state actors. Nonetheless, smuggling is a very pervasive phenomenon in West Africa which could impact state revenues, trade routes, consumption patterns, and wealth in the region. This study is based on a survey conducted by the Benin Institute of Statistics that attempts to record all illegal transactions at Benin’s borders for the span of one week. Our aim is to understand whether the quantity and/or the quality of the goods exchanged play a role in the determination of informal taxes. Better understanding the mechanisms driving the determination of the informal taxes will help authorities and local actors reduce informal trade.